What the Climate Wars Dave Done to Science. - RIDLEY, MATT (Quadrant Magazine, 2015)
The article offers the author's view on how the debate of climate change has affected the reputation of the study of science in Australia. The author states that it has put at risk of damaging the whole reputation of science. The author mentions that the debate has resulted in the democratisation of science by skeptic bloggers.